Chronic heart failure: Role of the GP in management. Issue 1 (1st February 2018) - Piterman, Leon; Yang, Hui; Yin, Zhaoxia
Abstract : The commonest cause of chronic heat failure in China is ischemic heart disease, followed by hypertension and valvular heart disease. Echocardiography is essential in establishing a diagnosis as well as helping to identify a cause and to monitor progress. Management includes nonpharmacological as well as pharmacological treatment, and self-care with careful monitoring of salt and fluid intake as well as regular weight measurement. Care planning and team-based care are essential in managing patients with chronic heart failure, who often have concurrent multimorbidity and are receiving polypharmacy. Significance statement: In keeping with the global rise in the prevalence of chronic and noncommunicable disease, the prevalence of chronic heart failure (CHF) is increasing globally, with estimates of 10% of the population older than 75 years affected in developed countries, despite improvements in the management of cardiovascular disease more generally. This article discusses current management of CHF, illustrating the important role played by the GP in coordinating care. Management includes nonpharmacological as well as pharmacological treatment, and self-care with careful monitoring of salt and fluid intake as well as regular weight measurement. Care planning and team-based care are essential in managing patients with CHF, who often have concurrent multimorbidity and are receiving polypharmacy.